THE TRANSLATION OF ENGLISH SLANG WORDS IN SIDNEY SHELDON "NOTHING LAST FOREVER" - Yuliana, Tiarma Ika (UG Journal, 2014)
The aim ofthe research is toind out what kind ofequivalence classification mostlyused in the translation of English slang words of"Nothing Lasts Forever" intoIndonesian. This research uses a text analysis with a descriptive qualitative methoddue to the problem statements. The data is 65 words and there are 11 words ofslang being analyzed into ive equivalents: denotative, pragmatic, connotative,textual, andformal equivalence. From the data, there are twelve slang wordsfoundin the novel. Among them, seven words appear more than two times than the other.Therefore, the writer will analyze seven of them. They are 'damn', fuck', 'hell','bastard', 'bitch', ,horny', and 'ass'. Finding shows that there are five types ofequivalence form in slang wordsfrom English into Indonesian, they are: 5 denotativeequivalence, 2 pragmatic equivalence, 2 connotative equivalence, 1 formalequivalence and 1 textual equivalence